A review of empirical research on ICT applications in teacher professional development and teaching practice - Dongpin Hu; Bei Yuan; Jiutong Luo; Minhong Wang (Knowledge Management & E-Learning: An International Journal, 2021)
The rapid development of information and communication technology (ICT) has been increasingly changing the ways of teaching and learning and teacher development. While the literature shows a proliferation of studies exploring various issues of applying ICT in teacher development and teaching practice, there is a lack of overview of the literature in this field. This study aimed to address the gap by reviewing the literature in two themes: (1) ICT in teacher professional development (TPD), and (2) ICT in teaching practice. Six journals of a high impact in the field of teaching and teacher education were selected, from which 85 articles involving ICT applications and published from 2013 to 2019 were identified. Among them, 18 empirical articles highly relevant to the two themes were analysed. The content analysis of these publications identified a set of specific ICT applications in TPD and in teaching practice. Moreover, the analysis revealed the key features of these ICT applications in terms of their functions, their effects on teaching and teacher development, the factors influencing their applications, and the problems in existing applications.